Effect of surfactants on the transport of polyethylene and polypropylene microplastics in porous media. (15th May 2021) - Jiang, Yanji; Yin, Xianqiang; Xi, Xianglong; Guan, Duo; Sun, Huimin; Wang, Nong
Highlights: CTAB and SDBS can suspend PE and PP microplastics well. PE and PP show a lower mobility in the presence of SDBS than CTAB. The migration capacity of PP is greater than that of PE. The XDLVO theory describes the transport behaviors of PE and PP well. The ADE model can fit the experimental data of PE and PP transport in CTAB well. Abstract: The transport of microplastics in porous media is attracting increasing attention. However, to date, research is limited to polystyrene microplastics. Meanwhile, surfactants can promote solid dispersion to form a stable suspension, possibly allowing microplastics to migrate when attached to a surfactant, which would increase the scope and degree of microplastic pollution, further endangering human health and the stability of the ecological environment. Therefore, in this study, the transport behavior of microplastics in porous media was explored in the presence of surfactants. Herein, polyethylene (PE) and polypropylene (PP) were evaluated while dispersed by two ionic surfactants: cationic surfactant-cetyltrimethylammonium bromide (CTAB) and anionic surfactant-sodium dodecylbenzenesulfonate (SDBS). The influence of different factors (surfactant concentration, ionic strength, pH, flow rate, and multivalent cations) on the transport of microplastics in porous media was explored via quartz sand packed-column experiments. Our experimental results show that the transport abilities of PE and PP increased with increasing surfactant concentration when the surfactant concentration was less than the critical micelle concentration (CMC). In the presence of CTAB and SDBS, physicochemical factors had different effects on the transport of microplastics mainly by controlling Zeta potential, advection diffusion and CMC. The mobility of PE and PP decreased with increasing ionic strength, cation valence and pH, and decreasing flow rate. However, the mobility of PE and PP under CTAB is much greater than that of PE and PP under SDBS, because quartz sand can absorb more CTAB molecules through electrostatic attraction to weaken the collision between microplastics and quartz sand. Further, the transport ability of PP was greater than that of PE under all conditions considered. Notably, the Extended-Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory formed by adding osmotic, elastic, and hydrophobic force could well described the migration behavior of microplastics in CTAB and SDBS well. This research highlights that surfactant has a significant impact on the transport ability of microplastics, and provides a comprehensive understanding of the migration and fate behaviors of microplastics affected by surfactants, which is necessary to prevent and reduce the environmental hazards of microplastics. Graphical abstract: Image, graphical abstract